2023
DOI: 10.14744/eej.2023.59672
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrogel Hyaluronic Acid on Dentine Sialophosphoprotein Expression of Human Dental Pulp Stem Cells

Valonia Irene NUGRAHENI

Abstract: Objective Hyaluronic acid (HA) is glycosaminoglycan and one of important factors in extracellular matrix. In an inflamed pulp, when niche biology is conducive, the recruitment of human dental pulp stem cells (hDPSCs) will take place and differentiate into odontoblast like cell, creating reparative dentine and expressing dentine sialophosphoprotein (DSPP). Therefore, the purpose of this study was to analyze the potential of hydrogel HA in various concentration towards hDPSCs differentiation via DSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…This is in agreement with Umemura et al [ 19 ] who reported that culturing human dental pulp stem cells (DPSCs) in HA reported an elevation in mineralization and ALP activity after 7 days. The results of our study are also consistent with the results obtained by Chen et al [ 20 ] who stated that the application of HMW-HA demonstrated an elevation in mineralization rate on day 7 using the ALP activity test, and Nugraheni et al [ 21 ] who stated that after 7 days of observation, HA application increased and stimulated odontoblast differentiation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with Umemura et al [ 19 ] who reported that culturing human dental pulp stem cells (DPSCs) in HA reported an elevation in mineralization and ALP activity after 7 days. The results of our study are also consistent with the results obtained by Chen et al [ 20 ] who stated that the application of HMW-HA demonstrated an elevation in mineralization rate on day 7 using the ALP activity test, and Nugraheni et al [ 21 ] who stated that after 7 days of observation, HA application increased and stimulated odontoblast differentiation.…”
Section: Discussionsupporting
confidence: 93%
“…Which can be related to a higher odontoblast differentiation rate. Nugraheni et al [ 21 ] stated that HA stimulates odontoblast differentiation up to 21 days of observation.…”
Section: Discussionmentioning
confidence: 99%